Two Novel katG Mutations Conferring Isoniazid Resistance in Mycobacterium tuberculosis - Hsu, Li-Yu; Lai, Li-Yin; Hsieh, Pei-Fang; Lin, Tzu-Lung; Lin, Wan-Hsuan; Tasi, Hsing-Yuan; Lee, Wei-Ting; Jou, Ruwen; Wang, Jin-Town (Frontiers in Microbiology, 2020)
Tuberculosis (TB), an infectious disease caused by Mycobacterium tuberculosis, is among the top 10 leading causes of death worldwide. The treatment course for TB is challenging; it requires antibiotic administration for at least 6 months, and bacterial drug resistance makes treatment even more difficult. Understanding the mechanisms of resistance is important for improving treatment. To investigate new mechanisms of isoniazid (INH) resistance, we obtained three INH-resistant (INH-R) M. tuberculosis clinical isolates collected by the Taiwan Centers for Disease Control and sequenced genes known to harbour INH resistance-conferring mutations. Then, the relationship between the mutations and INH resistance of these three INH-R isolates was investigated. Sequencing of the INH-R isolates identified three novel katG mutations resulting in R146P, W341R, and L398P KatG proteins, respectively. To investigate the correlation between the observed INH-R phenotypes of the clinical isolates and these katG mutations, wild-type katG from H37Rv was expressed on a plasmid (pMN437-katG) in the isolates, and their susceptibilities to INH were determined. The plasmid expressing H37Rv katG restored INH susceptibility in the two INH-R isolates encoding the W341R KatG and L398P KatG proteins. In contrast, no phenotypic change was observed in the KatG R146P isolate harbouring pMN437-katG. H37Rv isogenic mutant with W341R KatG or L398P KatG was further generated. Both showed resistant to INH. In conclusion, W341R KatG and L398P KatG conferred resistance to INH in M. tuberculosis, whereas R146P KatG did not affect the INH susceptibility of M. tuberculosis.